PvdA congres 10-12 april 1975 RAI Amsterdam. Voor v.ln.r. Peper, Vredeling, Den Uyl; daarchter v.l.n.r. Kurvers, Samkalden (1975)
PvdA congres 10-12 april 1975 RAI Amsterdam. Voor v.ln.r. Peper, Vredeling, Den Uyl; daarchter v.l.n.r. Kurvers, Samkalden.